Recent developments in physical invigoration techniques to develop sprouts of edible seeds as functional foods - Hassan, Sadia; Zeng, Xin-An; Khan, Muhammad Kamran; Farooq, Muhammad Adil; Ali, Amjad; Kumari, Ankita; Mahwish,; Rahaman, Abdul; Tufail, Tabussam; Liaqat, Atif (Frontiers in Sustainable Food Systems, 2022)
For nutritional security, the availability of nutrients from food sources is a crucial factor. Global consumption of edible seeds including cereals, pulses, and legumes makes it a valuable source of nutrients particularly vitamins, minerals, and fiber. The complexity of nutrients’ profile and the presence of anti-nutritional factors in edible seeds lead to reduced bioavailability of nutrients. By overcoming these issues, the germination process may help improve the nutrient profile and make them more bioavailable. Physical, physiological, and biological methods of seed invigoration can be used to reduce germination restraints, promote uniform plant stands, enhance early crop development, to increase yields and nutrient levels through sprouting. During sprouting early start of metabolic activities through hydrolytic enzymes and resource mobilization causes a reduction in emergence time which leads to a better nutrient profile. The use of physical stimulating methods to increase the sprouting rate gives several advantages compared to conventional chemical-based methods. The advantages of physical seed treatments include environment-friendly, high germination rate, early seedling emergence, uniform seedling vigor, protection from chemical hazards, and improved yield with a better nutrition profile. Different physical methods are available for seed invigoration viz. gamma irradiation, laser irradiation, microwaves, magnetic field, plasma, sound waves, and ultrasonic waves. The present review will describe the use and effects of physical processing techniques for seed invigoration.